The surface wind regimes on the northeast coastal of Kalimantan during 2016-2018. Issue 1 (May 2021) - Roem, Muhamad; Musa, Muhammad; Rudianto,; Risjani, Yenny
Abstract: This research aims to investigate the wind patterns in Northeast coastal of Kalimantan Island, known to border the western part of the Sulawesi Sea. Furthermore, the temporal wind patterns were examined based on the 2016-2018 recording data on Tarakan Island. The distribution of wind direction as well as speed were further analysed to obtain the monthly and seasonal wind pattern. The results show pattern complexity in the research area indicated by shifting in the monthly and seasonal wind resultant. This shift is particularly from the north, on instances where the Asian Monsoon is active, and conversely from the south at the Australian Monsoon peak. Meanwhile, during the transition period between monsoons, the wind blows weakly from various directions. However, the monsoon index value does not meet the criteria for the monsoon wind due to the influence of the sea breeze from the Sulawesi Sea throughout the year. Further analysis shows that the complexity of the local wind pattern is formed by sea breeze which is intertwined with monsoon winds.